HOW AI-ANALYTICS DRIVEN MARKETING BOOSTS ART-BASED CONTENT CREATORS' PERFORMANCE - Phelia Livia; Dewi Mustikasari Immanuel (LPPM STIE Muhammadiah Bandung, 2026)
The rapid growth of TikTok and Instagram as primary platforms for art marketing requires art-based content creators to adopt more data-driven and systematic marketing decision-making processes. However, limited resources, time constraints, and constantly evolving platform algorithms often reduce the effectiveness of intuition-based strategies. This study aims to examine the effects of AI-Analytics Adoption, Content Personalization, and Engagement Optimization on the Marketing Performance of art-based content creators. A quantitative cross-sectional research design was applied using a survey method involving 127 Indonesian art-based content creators who have utilized AI-based analytics tools. Data were analyzed using simple and multiple linear regression with JASP software. The findings reveal that all variables have a positive and significant effect on Marketing Performance. In the simultaneous model, AI-Analytics Adoption emerges as the strongest predictor, followed by Content Personalization and Engagement Optimization. Nevertheless, Content Personalization remains highly influential in enhancing engagement, reach, and commission conversion. These results highlight the importance of AI-driven analytics in supporting data-based marketing decisions for creators with limited resources. This study contributes to the literature by extending AI-based marketing strategies into the context of individual creators within the creative economy.